Assessment of Mycotoxin Contamination of Foods - Petrányi, Andrea; Boros, Norbert; Bodnár, Ildikó (International Journal of Engineering and Management Sciences, 2016)
According to RASFF reports, in the present, pathogenic microorganisms, pesticide residues and mycotoxins are the most frequent food contaminants. In 2014, 12% of the total notifications were caused by mycotoxin contamination. In this study we have analyzed the RASFF notifications that are related to the mycotoxin contaminations. It can be stated that aflatoxin is responsible for 90% of the total mycotoxin notifications, and the total notification number has decrease by 40% since 2004. However the number of oc hratoxin-A notifications are slowly increasing. Aflatoxin was mainly detected in nuts and nut products and oil seeds, especially groundnuts, while ochratoxin-A was detected in fruits (more than 85% in figs) and spices. The number of deoxynivalenol and fumonisin notifications were significantly less, however some appear every year for cereals and bakery products, especially corn and wheat. Zearalenone and patulin were detected only in 16 and 18 cases but 22% of the patulin notifications are related to baby food, so the tracking of patulin is really important.